Critique of Southern Society and Vision of a New Order: The Fellowship of Southern Churchmen, 1934–1957 - Martin, Robert F. (Church history, 1983)
Students of southern Protestantism seldom have interpreted regional Christianity, at least in its major denominational and sectarian expressions, as a force for positive economic or social change. Rather, they have correctly stressed its individualism, pietism, and fusion of religious and cultural values. Yet there have been a few Christians in the South who have been troubled by their region's mores and have boldly sought to change them. From the mid-1930s to the late 1950s a number of these individuals coalesced into a loosely knit interdenominational and interracial association, known after 1936 as the Fellowship of Southern Churchmen (FSC). Over the years this little cadre of Christians propounded a radical critique of twentieth-century southern civilization.